Future of Chinese Banking -- An Analysis of efficiency, determinants of profitability and influence of online financing and shadow banking - He, Rui (2016)
Abstract The purpose of this study is to predict the future of Chinese banking by analyzing determinants of profitability and the influence of online financing as well as shadow banking. The sample was formed by the data of 60 Chinese banks from the period of 2009 to 2014. An unbalanced panel data was gained from the original data. The parametric SFA(stochastic frontier approach) was applied for efficiency estimation and GMM (Generalize method of moments) was employed to find out determinants of profitability. In the second last part of the study, the influence of online financing and shadow banking were discussed from both positive and negative sides. The limitation of this study is the ignorance of risk taking in SFA modeling. In addition, we can only make discussion instead of statistic analysis due to the lack of specific data about shadow banking and online financing. In conclusion, our study suggests that Chinese banking sector would have a bright future with more diversification and high level of efficiency. Bank profitability can be adjusted by changing bank specific, industry specific and macro-economic determinants. Shadow banking and online financing would challenge traditional banking but also become a motivation of traditional banks development.